(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Oral health is an essential component of overall health and a satisfactory quality of life. The oral disease is termed as Mukharoga in Ayurveda. Gandusha is mentioned as one of the major therapies in Ayurveda medicine for both preventing and treating oral diseases. Acharya Sharangadara mentioned Triphala as a Gandusha and it consists of three myrobalans, which are Terminalia chebula, Terminalia bellerica, Phyllanthus emblica. Triphala is used as equal and unequal proportions. In the present study, Triphala mouth wash (TM) is prepared in the form of Kwatha (Decoctions) according to the Ayurveda Bhaisajyaratnavali. Then the same ingredients were used with different propotions to prepare the decoctions. They were considered as mouth wash based on the comments of Sharangadhara. The prepared decoctions were comparatively analyzed with standardization parameters. Decoctions were prepared in 3 ratios as follows: 1:1:1(TM1), 1:2:3 (TM2) and 1:2:4 (TM3) and assessed the organoleptic, physiochemical and phytochemical. Moreover, pharmacological properties were also evaluated using the authentic text books and the modern research findings. Dichlormethane fractions of Thriphala decoction in all three proportions were used to develop TLC and HPTLC fingerprints equivalent to gallic acid and tannic acid under the Toluene: Ethyl acetate: formic acid 2:5:1.5 solvent system. pH values of TM1, TM2 and TM3 were 3.98, 3.92, 3.96 respectively. The Foaming index was found to be less than 100 in all the three proportions. Phytochemical screening shows the presence of tannins, saponins, flavonoids etc. The TLC and HPTLC fingerprints showed the presence of tannic and gallic acid as active ingredients when visualized under UV at 254 and at 366 nm and the Triphala mouth wash prepared in 1:2:3 ratio showed the highest Rf values. Based on the pharmacological properties and actions, all the three proportions of Thriphala mouth wash can be used for oral diseases, but the effectiveness of therapeutic action may vary slightly according to the proportions of decoction. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">